Rural Education and the teaching of genetics: an investigative didactic possibility - Kássia Paula Oliveira da Silva; Lenicy Lucas de Miranda Cerqueira; Luciana Melhorança Moreira (Universidade Federal do Norte do Tocantins, 2021)
Research related to the genome project, cloning and genetically modified organisms are present inside and outside the school. Such subjects deserve attention in the teaching of genetics due to the difficulties presented by the students, regarding the learning of genetics in this subject, due to the high degree of abstraction, the impossibility of practical activities due to the planning and infrastructure necessary for its development. Understanding the challenges faced by teachers for the development of teaching strategies that ensure the learning of genetics, in a contextualized way, this work is developed. The objective of the described work was to elaborate and develop didactic strategies that allow the presentation of genetic contents in a contextualized way. An Investigative Didactic Sequence (SEI) was developed, in which the contents of Molecular Biology applied to Genetics were addressed in order to answer the question: "How to approach the concepts of Genetics to the context of students inserted in Rural Education?". It is a qualitative research of a participative nature, developed with students from the Education of the country, from the 3rd year of high school in Colniza/MT. It was observed that the students understood definitions such as: DNA, RNA, Chromosomes, Gene, Genome, as well as the perception of gene selection in the improvement of species and identified it as a recurrent practice in the area.